Islam, indigeneity, and religious difference in a secular context: Canadian case studies - Fachrizal Halim (Universitas Trunojoyo Madura, 2021)
This paper analyzes the hardening religious difference in contemporary Canadian society and explains why the presence of Muslims, including new converts, constantly incites in the public imagination the primordial threat of Islam to the secular accomplishments of Canadian society. Relying on the available data and previous research on the historical formation of the secular in Canada, the author attempts to detect a paradox within the statelead politics of recognition that unintentionally creates the conditions for new communal conflicts. By using an inductive generalization, the author argues that the perceived incompatibility between Islam and secular values is derived not so much from cultural and theological differences or actual political threats posed by Muslims or Indigenous converts. It instead emanates from the self-understanding of the majority of Canadians that defined the nation as essentially Christians and simultaneously secular.